What is this thing called science? - Chalmers, Alan F., 1939- (Maidenhead : Open University Press/McGraw-Hill Education, 2013)
Now well into its fourth decade, What is this thing calleds cience? has become a classic the world over. Each decade Alan Chalmers has drawn on his experience as a teacher and researcher to improve and update the text. In his accessible style, Chalmers illuminates the major developments in the field over the past few years. The most significant feature of this new, fourth edition is an extensive postscript, in which Chalmers uses the results of his recent research into the history of atomism to illustrate and enliven key themes in the philosophy of science. Identifying the qualitative differences between knowledge of atoms as it figures in contemporary science and metaphysical speculations about atoms common in philosophy since the time of Democritus proves to be a highly revealing and instructive way to find answers to the question "What is this thing called science?".
1. Science as knowledge derived from the facts of experience -- 2. Observation as practical intervention -- 3. Experiment -- 4. Deriving theories from the facrs: induction -- 5. Introducing falsificationism -- 6. Sophisticated falsificationism, novel predictions and the growth of science -- 7. The limitations of falsificationism -- 8. Theories as structures I: Kuhn's paradigms -- 9. Theories as structures II: research programs -- 10. Feyerabend's anarchistic theory of science -- 11. Methodical changes in method -- 12. The Bayesian approach -- 13. The new experimentalism -- 14. Why should the world obey laws? -- 15. Realism and anti-realism -- 16. Epilogue to the third edition -- 17. Postscript
Keywords: Vetenskapsteori; Kunskapsteori; Research Design; Research -- methods; Science -- methods; Knowledge, Theory of; Kunskapsteori; Vetenskapsteori; Philosophy of science; Miscellaneous